Enhancement of Graphite Functionality in Renewable Polymer Composite Properties - Munirah Abdullah, Nur; Z. M. Rus, A; F. L. Abdullah, M (International Journal of Engineering and Technology, 2018)
The preparation and characterization of composite thin films of renewable polymer graphite (PG) is disclosed. Thin films ~ 0.1 mm thick are prepared using a simple solution mixing with mass proportion of 2/1 (renewable monomer/ Methylene Diphenyl Diisocyanate, MDI), upon differ graphite content (PG0, PG5, PG10, PG15, PG20, PG25 andPG30) and drop casting at room temperature. The morphology-structure relations of renewable PG composites with respect to electrical conductivity were diagnosed using Optical microscope (OM), Fourier transform infra-red spectroscopy (FTIR) and Thermogravimetric analysis (TGA). The homogeneous random dispersion and strong interface between the graphite in the classical insulating renewable polymer matrix were observed. Thus resulting of enhancements in thermal stability with slight shift of decomposition temperature and better mechanical properties through the modulus and tensile strength increment up to ~440% and ~100% respectively. The result shows that it can simultaneously leads to renewable PG conductivity (Ïƒ) where the percolation threshold occurs at higher graphite content (PG20, PG25 andPG30) of 103 - 104 S/m. Thus, this non-petroleum based renewable polymer graphite composites have remarkably more to offer as conducting polymer composites material in multidisciplinary applications.Â